2011
DOI: 10.1161/strokeaha.111.620187
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Cardiac Rehabilitation for Secondary Prevention After Transient Ischemic Attack or Mild Stroke

Abstract: Background and Purpose-Comprehensive cardiac rehabilitation (CCR), which integrates structured lifestyle interventions and medications, reduces morbidity and mortality among cardiac patients. CCR has not typically been used with cerebrovascular populations, despite important commonalities with heart patients. We tested feasibility and effectiveness of 6-month outpatient CCR for secondary prevention after transient ischemic attack or mild, nondisabling stroke. This article presents risk factors. A future articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 42 publications
(31 reference statements)
1
78
0
Order By: Relevance
“…210,211 Several studies have shown that aerobic exercise and strength training will improve cardiovascular fitness after stroke. 197,[210][211][212][213][214][215] Structured programs of therapeutic exercise have been shown to improve mobility, balance, and endurance, 213 and beneficial effects have been demonstrated in different ethnic groups and in both older and younger patients. 216 Together, these studies provide important information on the safety and selected clinical benefits of exercise after stroke.…”
Section: Strokementioning
confidence: 99%
“…210,211 Several studies have shown that aerobic exercise and strength training will improve cardiovascular fitness after stroke. 197,[210][211][212][213][214][215] Structured programs of therapeutic exercise have been shown to improve mobility, balance, and endurance, 213 and beneficial effects have been demonstrated in different ethnic groups and in both older and younger patients. 216 Together, these studies provide important information on the safety and selected clinical benefits of exercise after stroke.…”
Section: Strokementioning
confidence: 99%
“…The use of a comprehensive exercise and lifestyle program modeled after cardiac rehabilitation in people after a TIA and mild stroke was shown to yield improvements in total cholesterol, body composition, blood pressure, and behavior change toward nonsmoking. 68 Physical activity can be effective only if it is done consistently. Unfortunately, although physical activity is clearly established and widely recognized as a means to reduce the risk of stroke and other CVDs in virtually all individuals, sedentary behaviors remain a persistent and significant problem for the general population, and even more so for chronic disease populations, including those with stroke.…”
Section: Importance Of Comprehensive Stroke Care and Cvd Risk Reductionmentioning
confidence: 99%
“…Studies have established the feasibility and effectiveness of adapting exercise-based cardiac rehabilitation interventions for individuals with mild to moderate disability from stroke, 172,207 and comprehensive models that integrate exercise, lifestyle modification, and medications have been shown to be beneficial for individuals after TIA or stroke with little to no residual deficits. 68,208 Larger clinical trials are currently under way to examine whether similar models of care involving exercise and risk factor modification can be adapted and implemented among individuals with TIA or a broader range of clinical presentation after stroke. 209,210 These trials represent important steps toward the development of optimal secondary prevention strategies that integrate exercise interventions into a comprehensive risk-reduction program for stroke survivors.…”
Section: Exploring Effective Models Of Carementioning
confidence: 99%
“…Participation in CR programs have been shown to reduce mortality by about 25%-30% and to have favorable effects on re-hospitalization and functional capacity (Grace et al, 2008). Emerging evidence supports the feasibility, safety and benefits of CR for transient ischemic attack/mild non-disabling stroke patients as well (Lennon et al, 2008;Prior et al, 2011;Tang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…CAD and transient ischemic attack or mild, non-disabling stroke have similar atherosclerotic etiology and modifiable risk factors. As such, similar to secondary prevention for CAD, recurrent vascular events in stroke patients can be prevented with an exercise-based, lifestyle intervention in combination with medication therapies (Prior et al, 2011;Sacco et al, 2006).…”
Section: Introductionmentioning
confidence: 99%